2015
DOI: 10.1080/02673037.2015.1114076
|View full text |Cite
|
Sign up to set email alerts
|

Straight-line Assimilation in Leaving Home? A Comparison of Turks, Somalis and Danes

Abstract: The purpose of this paper is to test the evidence for spatial assimilation and straightline assimilation in the transition of leaving home in Denmark. Based on data from the extensive Danish registers, the paper analyses the home-leaving patterns of Danes, Turkish immigrants, Turkish descendants and Somali immigrants. Two main findings emerged. First, while spatial segregation patterns of home-leavers were clear, inter-generational mobility did take place, supporting the notion of straight-line assimilation. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(47 reference statements)
0
7
0
1
Order By: Relevance
“…A large number of studies have found evidence of spatial assimilation, both in North America (Massey & Denton, ; Pais, South, & Crowder, ; South et al, ) and in Europe (Feng et al, ; Macpherson & Strömgren, ; Musterd & van Gent, ; Silvestre & Reher, ; Skifter Andersen, ; Skifter Andersen, ; Skovgaard Nielsen, ; Valk & Willaert, ). However, the empirical results regarding the relationship between time and spatial assimilation are mixed.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…A large number of studies have found evidence of spatial assimilation, both in North America (Massey & Denton, ; Pais, South, & Crowder, ; South et al, ) and in Europe (Feng et al, ; Macpherson & Strömgren, ; Musterd & van Gent, ; Silvestre & Reher, ; Skifter Andersen, ; Skifter Andersen, ; Skovgaard Nielsen, ; Valk & Willaert, ). However, the empirical results regarding the relationship between time and spatial assimilation are mixed.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…However, the empirical results regarding the relationship between time and spatial assimilation are mixed. A number of studies have found support for spatial assimilation, showing that the level of residential segregation decreases with the duration of residence in the host country (Edgar, ; Silvestre & Reher, ; Skovgaard Nielsen, ; South et al, ). Also in line with spatial assimilation, second‐generation migrants have been found to be more likely than first generation ones to reside in native‐dominated suburban areas (Andersson, ; Edgar, ; Musterd & van Gent, ; Valk & Willaert, ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations